La via pulchritudinis: ecos de trascendencia = Abweichender Titel: The Via pulchritudinis : Echoes of Trascendence - García Lozano, Francisco José (Cauriensia, 2025)
The aesthetic dimension of life is continually present in human activity. It is therefore a universal path. This article addresses the path of beauty as an alternative to the exhaustion of discursive paths of access to transcendence. In recent decades, the path of beauty has been acquiring an increasingly relevant role in theological reflection and as a path of evangelization. If beauty can be considered one of the privileged paths of being, it can also be the path of recovery of the foundation of the rest of the transcendentals, light that gives rise to the action of good (ethics) and to the occurrence of truth (theoretical).